A dataset of transcriptomic effects of camptothecin treatment on early zebrafish embryosGene Expression Omnibus - Sergey V. Prykhozhij; Kevin Ban; Zane L. Brown; Kim Kobar; Gabriel Wajnberg; Charlotte Fuller; Simi Chacko; Jacynthe Lacroix; Nicolas Crapoulet; Craig Midgen; Adam Shlien; David Malkin; et al. (Data in Brief)
Zebrafish (Danio rerio) are a good model for cancer research including studies on chemotherapy treatments. We treated wild-type and miR-34a deletion mutant zebrafish embryos at 24 h post-fertilization with 1 µM of the topoisomerase I inhibitor, camptothecin (CPT), for 4 h to catalogue gene expression changes induced by this DNA damage treatment and to understand if these changes are influenced by loss of miR-34a. The 4 sample groups of 3 independent biological samples consisting of 30 embryos each were analyzed by RNA-sequencing using the recently updated zebrafish transcriptome annotation based on GRCz11, which enabled a more complete and sensitive read mapping and gene assignment than standard annotations. Using this gene expression estimates dataset as the primary resource, we performed a differentially expressed gene (DEG) analysis based on treatment as loss of miR-34a had minimal effects on CPT-induced expression changes. The DEGs were analyzed for Gene Ontology and KEGG pathway terms. Enriched terms and pathways among up-regulated genes were mostly related to stress, cell death, cell cycle regulation, transcriptional regulation, cell signalling, developmental processes and synthesis of retinol and steroid hormones. By contrast, down-regulated genes were most strongly associated with genes involved in key developmental processes, adhesion molecules, as well as some transport and metabolic pathways, together suggesting a “developmental shutdown”. We also identified interferon-regulated genes and p53 target genes activated or inhibited by DNA damage due to topoisomerase I inhibition, suggesting that they are important components of the response to this type of DNA damage in zebrafish embryos.